Exact Microsatellite Density Differences among Capsicum Tissues and Development Stages - Ahmet Onus; Ayşe İnce; Mehmet Karaca (Journal of Agricultural Sciences)
Density and position differences of microsatellites in genomes may indicate important roles of microsatellites in genetic development and regulation of gene expression. However, there is no or limited study on microsatellite density differences among tissues of development stages. In the present study, exact microsatellite densities and motifs among 7 different tissues and development stages were determined using Capsicum annuum L. expressed sequence tags (ESTs), which were reassembled into in silico libraries. Results indicated that densities of exact microsatellites (1 to 6 bp repeats) in housekeeping and tissue specific ESTs of anther, flower bud, and placenta specific ESTs were statistically different, being low in comparison to that of leaf, fruit, early and hairy root. Further analyses also indicated that exact microsatellite density of anther and placenta was significantly low while exact microsatellite density of flower bud, early and hairy root was significantly higher. There were density differences among mono-, di-, tri- and hexa-nucleotides between housekeeping and tissue specific ESTs. Density of tri- and penta-nucleotides was not statistically significant. Overall results of the present study indicated that since the microsatellite densities differed between housekeeping and tissue specific genes, genes containing microsatellites may differ among tissues and development stages.